Empowering Digital Learning UMPSAs Synergy in EdTech Initiatives for Micro-Credential Content Development - Amy Zulaikha, Mohd Ali (UMPSA, 2023)
KUANTAN, 6 July 2023 - When push comes to shove, humans adapt. In today’s digital age, where online education is pertinent, initiatives to provide exceptional digital content and enhance the overall learning experience stand out as a testament to Universiti Malaysia Pahang Al-Sultan Abdullah’s unwavering commitment to achieving UMPSA25 strategic planning.